The Role of Serfdoms in the Obligation System of the Inhabitants of Villages on the Wallachian Law in Lesser Poland (Małopolska) and Crown Ruthenia (15th-16th century). - Jawor, Grzegorz (Balcanica Posnaniensia. Acta et studia, 2020)
The Role of Serfdoms in the Obligation System of the Inhabitants of Villages on the Wallachian Law in Lesser Poland (Małopolska) and Crown Ruthenia (15th-16th century). The aim of the article is an attempt to define a role of serfdoms in the system of obligations provided by the population living in the settlements established on the Wallachian law. On the basis of a critical analysis of a relatively numerous sources preserved from the region in question (in particular, the documents associated with the rights given to individual villages, inventories, and royal domain), an attempt was made to verify the common belief in the scholarship on this topic about the lack of, or at least the minimum, share of the serfdoms for the owners in the obligation system of the inhabitants. As a result, a specific feature of the Wallachian law was indicated, which was the obligation – elsewhere unknown or occurring only in minute traces – of performing small errands a few times in a year for the benefit of the dukes (kniaź). It was recorded throughout the entire studied period and in all of the areas partaking in the Wallachian colonisation. In contrast, there are many more doubts regarding the conviction about a complete lack of serfdoms for the owners of villages. The presented source material indicates that there were indeed settlements to which this duty did not apply (and perhaps this situation was even dominating), but in other places the older and usually less strenuous forms of labours were present (annual works, duties “under the order”, ect.), while the attempts to impose weekly serfdoms date back to the 1530s and 1540s. Its widespread implementation in the areas outside of mountains is strictly linked to the development of a grange, set up for the production of grain. For the Wallachian settlements this meant a limitation, and then a thorough disposal of their privileged legal status. It is not a matter of coincidence that this colonising tendency was clearly restrained at the turn of the 16th and 17th century. This fate was avoided only be the villages situated in a typically mountainous area where the natural conditions prevented the production of crops on a large scale. Populations living therein – that were ruled by the Wallachian law – lasted longer and the processes of assimilation and integration with the local surroundings took place more slowly. .